Career-Related Predictors of Work-Bound and College-Bound Status of Adolescents in Rural and Nonrural Areas - Jay W. Rojewski (Journal of Research in Rural Education, 1999)
Datafrom the National Education Longitudinal Study: 1988-94 was used to examine career-related characteristics and postsecondary attainment status (work-bound or college-bound) ofrural and nonrural youth involved in the transition from school to work. Rural youth were more likely to be work-bound than nonrural youth. Socioeconomic status (SES) had considerable influence in predicting transition path status. Individuals in the lowest SES quartile were twice as likely to be work-bound, while adolescents in the highest SES quartile were four times more likely to be college-bound. Work-bound youth reported greater involvement in vocational education. Prediction accuracy and variable importance werefairly consistentfor college-bound and work-bound adolescents, although somewhat dependent on rural and nonrural residence. Occupational aspirations was the single best predictor oftransition status for college-bound individuals. SES was the best predictorfor rural work-bound youths. while SES and participation in vocational education were the best predictors ofwork-bound status for nonrural adolescents.